2021
DOI: 10.1177/00405175211046060
|View full text |Cite
|
Sign up to set email alerts
|

Image classification method of cashmere and wool based on the multi-feature selection and random forest method

Abstract: Cashmere and wool play an important role in the wool industry and textile industry, and suitable features are the key to identifying them. To obtain effective features and improve the accuracy of cashmere and wool classification, the multi-feature selection and random forest method is used to express in this article. Firstly, the gray-gradient co-occurrence matrix model is used for texture feature extraction to construct the original high-dimensional feature data set; secondly, considering that the original fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Finally, the improved random forest algorithm was used to classify images. The research outcomes demonstrated that the IR model made the classification accuracy of cashmere and wool higher, about 90% 5 . Zhu et al designed an IR method for cashmere and wool fibers based on an improved Xception network.…”
Section: Related Workmentioning
confidence: 96%
“…Finally, the improved random forest algorithm was used to classify images. The research outcomes demonstrated that the IR model made the classification accuracy of cashmere and wool higher, about 90% 5 . Zhu et al designed an IR method for cashmere and wool fibers based on an improved Xception network.…”
Section: Related Workmentioning
confidence: 96%
“…Its complex depth structure is the reason for the slowdown of YOLOv3 training and detection 28 . Five down-sampling times are carried out in the network, and the features are output in the last three layers, and three scales of YOLO layers are generated after processing in the pyramid feature space 29 , 30 . Darknet-53 dominates the feature extraction work, and the YOLO layer is responsible for the interaction between the different feature layers.…”
Section: Improved Yolo Lightweight Model Design For Intelligent Stati...mentioning
confidence: 99%